2016
DOI: 10.1007/s12265-016-9711-3
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Model of Mouse Cardiac Myocyte Senescence

Abstract: Many cardiac aging studies are performed on mice first and then, due to difficulty in mouse cardiomyocyte culture, applied the rat neonatal cardiomyocytes to further determine the mechanisms in vitro. Now, the technological challenge of mouse cardiomyocyte culture has been overcome and there is an increasing need for the senescence models of mouse cardiomyocytes. In this study, we have demonstrated that the senescence of mouse cardiomyocytes occurred with the extended culture time as shown by the increased β-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Overall, our results correspond with Wang et al, who have already described the culture of neonatal cardiomyocytes derived from C57Bl/6 mice over 28 days as a model system of cardiac senescence[40]. The herein presented results supplement the literature by the data of p16, p21 and autofluorescence in cultured neonatal cardiomyocytes and clarify the temporal course of the commonly used markers of cellular senescence over 21 days.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Overall, our results correspond with Wang et al, who have already described the culture of neonatal cardiomyocytes derived from C57Bl/6 mice over 28 days as a model system of cardiac senescence[40]. The herein presented results supplement the literature by the data of p16, p21 and autofluorescence in cultured neonatal cardiomyocytes and clarify the temporal course of the commonly used markers of cellular senescence over 21 days.…”
supporting
confidence: 91%
“…In contrast to their adult state, mammalian neonatal cardiomyocytes allow the maintenance of a prolonged, physiologically contractive culture [36]. Murine neonatal cardiomyocytes have already been used to mimic diverse states of cardiac dysfunction, such as myocardial ischemia [37], ventricular hypertrophy [38], arrhythmia [39], and cellular senescence [40]. As studies on protein homeostasis (proteostasis) and contractility in cardiomyocyte aging remain a challenging task, culture of neonatal cardiomyocytes offers an optimal approach for manipulation studies under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that not only mitotic, but also postmitotic cells are capable of entering a state of senescence. This has been observed in a number of cell types from the CNS (Jurk et al, 2012), bone (Farr et al, 2017), cardiac (Wang et al, 2016), and adipose tissue (Minamino et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…This has been observed in a number of cell types from the CNS (Jurk et al, 2012), bone Figure S7. (Farr et al, 2017), cardiac (Wang et al, 2016), and adipose tissue (Minamino et al, 2009).…”
Section: Discussionmentioning
confidence: 99%